2007
DOI: 10.1200/jco.2007.10.9231
|View full text |Cite
|
Sign up to set email alerts
|

Donepezil for Cancer Fatigue: A Double-Blind, Randomized, Placebo-Controlled Trial

Abstract: Donepezil was not significantly superior to placebo in the treatment of cancer-related fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(56 citation statements)
references
References 27 publications
1
52
0
3
Order By: Relevance
“…However, as some studies showed considerable response to placebo, using appropriate placebo treatment should be considered in the future studies. 29,30 Another limitation is the two week treatment period without follow-up. While many studies use 1-or 2-week treatment period in the clinical trial setting, 30,31 it would be appropriate in the future studies to administer for longer periods of time with longterm follow-up research as fatigue is a rather chronic symptom and in most cases, affecting the patients longer than several weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as some studies showed considerable response to placebo, using appropriate placebo treatment should be considered in the future studies. 29,30 Another limitation is the two week treatment period without follow-up. While many studies use 1-or 2-week treatment period in the clinical trial setting, 30,31 it would be appropriate in the future studies to administer for longer periods of time with longterm follow-up research as fatigue is a rather chronic symptom and in most cases, affecting the patients longer than several weeks.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Another limitation is the two week treatment period without follow-up. While many studies use 1-or 2-week treatment period in the clinical trial setting, 30,31 it would be appropriate in the future studies to administer for longer periods of time with longterm follow-up research as fatigue is a rather chronic symptom and in most cases, affecting the patients longer than several weeks. A recent study by Kobayashi et al 32 also adopted a longer administration protocol with Bojungikkitang, which is considered to work in a slower manner.…”
Section: Discussionmentioning
confidence: 99%
“…We chose the FACIT-F score as the primary outcome measure because it has been widely used in CRF treatment trials by our team and others. [40][41][42][43] Test-retest reliability coefficients for the FACIT-F have ranged from .84 to .90. 44 This scale has been shown to have strong internal consistency (α = .93-.95) and has a sensitivity of 0.92 and specificity of 0.69.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…The time frame evaluated varied from hours [28,53] to months [52,64]. Some symptom toxicity instruments, like Morrow Assessment of Nausea and Emesis (MANE) [67,72,73], Worthing Chemotherapy Questionnaire (WCQ) [52], and single ESAS items considered specific treatment-related change ( Table 2).…”
Section: (B) Factor Analysismentioning
confidence: 99%